Incidence of Simian Crease in Normal Nepalese Children - Malla, T; Malla, K K; Gauchan, E; Brijesh, S; Sharma, R (Kathmandu University Medical Journal, 2012)
Backgroud Simian crease is usually associated with some chromosomal anomalies and syndromes but it is also seen in some populations without any chromosomal defects. Objective To see the incidence of simian crease in children without chromosomal anomalies and to detect the Ethnic group variations. Methods A prospective study in children attending the paediatric outpatient department of Manipal Teaching Hospital, Pokhara. –2,067 children were screened randomly from the 1st June 2007 to the 31st December 2007. Palm crease and axial triradius angle were detected in every child. Axial Triradius angle was compared between those who have simian crease to those who do not simian crease.Children who were found with simian crease underwent IQ testing. The exclusion criteria were children with Down syndrome, other chromosomal and minor anomalies, plus or any other chronic disease condition. Results 2,067children (1,084 boys & 983 girls) were screened. Among them four were cases of Down syndrome so were excluded from the study. Finally total of 2,063 (1,082 boys & 981 girls) were the study group. There were a total 14 ethnic groups who attended the outpatient department of Manipal Hospital during a seven months period. Among the seven ethnic groups Brahaman, Gurung, Tamang, Lama, Newar, Chettri and Dalit had single palmar crease. The incidence of simian crease was14.6%.This incidence was highly significant (p<0001) in Lama population (71.2%). In these seven ethnic groups axial triradius angle was compared between those who had simian crease and with those who did not have simian crease. Comparisons were made statistically and found to be significant. Conclusion Incidence of simian crease in Nepalese children was 14.6% and was observed only in certain ethnic groups. It was significantly high in the Lama population (71.2%0. http://dx.doi.org/10.3126/kumj.v8i4.6241 Kathmandu Univ Med J 2010;8(4):410-14